Efficacy and safety of immune checkpoint inhibitors combined with chemotherapy in patients with extensive-stage small cell lung cancer: a systematic review and meta-analysis of randomized controlled trials - Chen, Chunlan; Tian, Peng; Zhong, Jiangshan; Fan, Xianming (Frontiers in Oncology, 2023)
Background: Approximately 60-70% of patients with small cell lung cancer are diagnosed with extensive-stage small cell lung cancer (ES-SCLC) at initial diagnosis, and the first-line chemotherapy has not enhanced the life expectancy, so it is imperative to ascertain the efficacy and safety of other practical treatments for ES-SCLC patients. Objective: This study aimed to look into the clinical efficacy and safety of immune checkpoint inhibitors (ICI) in combination with chemotherapy versus chemotherapy alone in the first-line treatment for ES-SCLC. Methods: PubMed, Embase, ClinicalTrials, and CNKI databases were searched to collect relevant research published up to September 17, 2022. After two investigators independently screened the literature, extracted information, and evaluated the risk of bias in the included studies, this Meta-analysis was performed using RevMan 5.4 software. Overall survival (OS), progression-free survival (PFS), overall response rate (ORR), and adverse events were compared between those groups in ES-SCLC patients receiving first-line chemo-immunotherapy. Results: A total of 8 studies including 3952 patients were included. Meta-analysis results showed that compared with the chemotherapy alone (control group), the ICIs combined with the chemotherapy (experimental group) significantly improved the OS(HR=0.78, 95% CI (0.72-0.85), P<0.05), PFS(HR=0.72, 95% CI (0.63-0.83), P < 0.05), ORR( 68.2 % VS 62.2%), and the incidence of grade 3 and higher adverse events was not significantly increased ( RR=1.06, 95 % CI (1.00 to 1.12), P =0.04). Subgroup analysis showed that the PD-1/PD-L1 group was superior to the CTLA-4 group in terms of OS, ORR, and safety. Conclusion: Compared with chemotherapy alone, immune checkpoint inhibitors combined with chemotherapy can be a better option for extensive-stage small-cell lung cancer.